Current uses of intracranial vessel wall imaging for clinical practice: a high-resolution MR technique recently available - PACHECO, Felipe Torres; CRUZ, Luiz Celso Hygino da, JUNIOR; PADILHA, Igor Gomes; NUNES, Renato Hoffmann; MAIA, Antônio Carlos Martins, JUNIOR; CAMPOS, Christiane Monteiro Siqueira; AMARAL, Lázaro Luís Faria do; MASSARO, Ayrton Roberto; ROCHA, Antônio José da (Arquivos de Neuro-Psiquiatria, 2020)
Intracranial vessel wall imaging plays an increasing role in diagnosing intracranial vascular diseases. With the growing demand and subsequent increased use of this technique in clinical practice, radiologists and neurologists should be aware of the choices in imaging parameters and how they affect image quality, clinical indications, methods of assessment, and limitations in the interpretation of these images. Due to the improvement of the MRI techniques, the possibility of accurate and direct evaluation of the abnormalities in the arterial vascular wall (vessel wall imaging) has evolved, adding substantial data to diagnosis when compared to the indirect evaluation based on conventional flow analyses. Herein, the authors proposed a comprehensive approach of this technique reinforcing appropriated clinical settings to better use intracranial vessel wall imaging.
Keywords: Magnetic Resonance Imaging; Stroke; Intracranial Arteriosclerosis; Vasculitis